(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The present study investigated the effect of reinforcing contingencies on the increase in the prosocial behavior of students in the school context. Radical Behaviorism has a powerful arsenal to contribute to improvement in Education, especially the positive reinforcement principle. Twenty students, three teachers and the school co-coordinator participated in this study. The experimental conditions were: Baseline and intervention, presentation of the principles of experimental analysis to teachers and the school coordinator and the practice of activities that focus on pro-social behavior with the students. The results indicate a reduction in the frequency of anti-social behavior, an increase in pro-social behavior, increased student participation in the schools program of activities and a reduction in the frequency of aversive control by teachers. These data confirm that reinforcing contingencies were effective in strengthening pro-social behavior.